Evaluation of Anti-icing Emulsified Asphalt Binders - Shan, Liyan; Yang, Hu; Tian, Dong; Tan, Yiqiu (Frontiers in Materials, 2020)
Snow and ice on asphalt pavement surface can significantly affect traffic safety and damage pavements. To reduce its effect, a kind of anti-icing emulsified asphalt binder (AEAB) is developed by adding a certain amount of anti-icing fillers to the modified emulsified asphalt binder. The anti-icing performance and pavement performance of AEAB coating are evaluated. The results show that: the basic properties of AEAB meet the requirement of road maintenance, and the AEAB has excellent anti-icing performance and bonding property. It can facilitate the ice-melting on pavement and reduce the adhesion force between pavements and ice, and the adhesion force can be reduced by about 50%. The AEAB coating can keep an excellent bonding state with the original pavement, which can prolong the service life of the coating. These findings demonstrated the potential of using AEAB coating on asphalt pavement to provide better pavement performance and contribute to traffic safety during snowfall.